Health-related quality of life based on KIDSCREEN-52 in stuttering children and adolescents - ÖZGÜR, Erdoğan; GÜRBÜZ ÖZGÜR, Börte (ENT Updates, 2020)
Objective: Stuttering is a communication disorder that can affect an individual’s life in many ways. This study aimed to evaluate the effects of stuttering on children and adolescents’ health-related quality of life (HRQoL). Methods: This is a cross-sectional type of case-control study. Thirty-six children and adolescents diagnosed with stuttering according to DSM-5 and 37 age- and gender-matched healthy children and adolescents were included in the study. The child and adolescent’s HRQoL in both groups was evaluated using the KIDSCREEN-52 self and proxy reports. Results: No significant difference was observed in the physical well-being, psychological well-being, moods and emotions, self-perception, autonomy, parental relationships and home life, financial resources, social support and peers, school environment, social acceptance-bullying dimensions in the KIDSCREEN-52 questionnaire between-group comparison of both report and proxy results. The parental score reports were found to be statistically significantly lower than the children with stuttering in social acceptance-bullying dimension. In contrast, the children’s scores in the dimensions of physical well-being, self-perception, parental relationships and home life, social support and peers and school environment were found to be statistically significantly lower than their parents. Conclusion: According to the study results, it was observed that the HRQoL of children between the ages of 8-18 who stutter was not different from healthy children. Since factors affecting the HRQoL of children may be affected by developmental processes, the necessity of longitudinal assessment of the HRQoL of stuttering children should be considered.